Cross‐linking for the analysis of α‐synuclein in the enteric nervous system. Issue 5 (4th October 2016) - Corbillé, Anne‐Gaëlle; Neunlist, Michel; Derkinderen, Pascal
Abstract : Aggregated α‐synuclein is found in the gut in almost all Parkinson's disease patients. We used amine‐reactive cross‐linking to study the native state of α‐synuclein in the enteric nervous system (ENS). We showed that, by contrast to erythroid cells and brain neurons, α‐synuclein exists primarily as a monomer in intact enteric neurons. Our results provide new insights into the possible role of the ENS in the pathophysiology of Parkinson's disease. Abstract: Since the observation that aggregated α‐synuclein, the pathological hallmark of Parkinson's disease (PD), is found in the gut in almost all patients, it has been suggested that the enteric nervous system (ENS) could be a starting point for α‐synuclein pathology. α‐synuclein has long been thought to occur as a monomer in living cells, but recent studies reported that it instead exists as a tetramer in non‐neuronal cells and in neurons. Given the possible key role of the ENS in PD pathophysiology, we undertook the current research to characterize the native state of α‐synuclein in rat primary culture of ENS and in adult human healthy ENS. Using amine‐reactive cross‐linking, we showed that, by contrast to cell lines and brain neurons, α‐synuclein exists primarily as a monomer in intact enteric neurons, suggesting that the native state of α‐synuclein is different between the ENS and the brain. Our results provide new insights into the widely discussed concepts of α‐synuclein aggregation and misfolding in PD and raise issue about the possible transmission of α‐synuclein from the ENS to the brain.